Cyclic behaviour of UHPC columns with hybrid CFRP/Steel reinforcement bars. (1st July 2021) - Hu, Rui; Fang, Zhi; Benmokrane, Brahim; Fang, Wenchang
Highlights: A new kind of structural system, UHPC columns with hybrid reinforcement, is proposed; Quasi-static tests of four UHPC columns with hybrid reinforcement are conducted; Influences of CFRP bars and axial-load ratio on the UHPC columns are analyzed; The design axial-load ratio limit of the hybrid UHPC columns is proposed; A proper replacement ratio of CFRP bars was suggested for the hybrid UHPC columns. Abstract: A new type of reinforced concrete column with ultra-high-performance concrete (UHPC) and hybrid carbon fibre-reinforced polymer (CFRP) and steel bars is proposed in this paper. The CFRP bars with an excellent linear elastic property are used in the columns to enable the expected self-centring capacity. Steel bars with good plastic properties and high ductility UHPC were used to maintain the high energy-dissipation capacity of the columns. Four UHPC columns were tested under reversed cyclic lateral loading; the behaviour of the UHPC columns with hybrid CFRP/steel reinforcement bars was analysed numerically using OpenSees, and the influences of the CFRP bars and axial-load ratio on the seismic behaviour of the columns were analysed. The results indicate that the strain in the longitudinal bars at the ultimate state is a crucial criterion for determining the effectiveness of the CFRP bars. The UHPC columns with the hybrid CFRP/steel reinforcement exhibit both excellent self-centring capacity and good energy dissipation when the design axial-load ratio is less than 0.7. The replacement ratio of the CFRP bars is suggested to be 1/3–2/3 so that the self-centring and energy-dissipation capacity of the UHPC columns with hybrid CFRP/steel reinforcement bars can be balanced.